New Zealand’s Trade Prospects in an Uncertain Trans-Pacific Partnership (TPP) Environment: Results from Gravity Model - Shakur S; Tsang CY (Massey University)
Abstract: This paper applies a modified gravity model to assess trade patterns between New Zealand and its major trading partners, including potential TPP members using annual pre-agreement data for the period 2000-2015. Although the Agreement, in its current form, cannot enter into force without the US participation, the remaining members have reaffirmed their commitment to TPP. The assumptions of the traditional gravity model that economic size would positively affect bilateral trade flows between countries while distance would negatively affect this outcome was tested. Results from this research suggest that New Zealand tends to trade more with larger countries and having free trade agreement with major Asia-Pacific countries will enhance New Zealand’s merchandise trade, especially exports of agricultural products. At another level, trade intensity index (TII) and the revealed comparative advantage (RCA) between New Zealand and potential TPP members were also calculated in this research. When applied to potential TPP countries, calculated TIIs show that there is not enough evidence to suggest that TPP would necessarily improve New Zealand’s trading relationship with member countries, yet it would reinforce the existing trade patterns. Calculated RCAs in this research indicate that the trade creation effects are likely to be larger than trade diversion effects. Generally speaking, the TPP countries are sharing different RCA in different product groups. Although the status of TPP remains uncertain at this time, this study could provide some useful predictions about the likely trade effects on New Zealand merchandise trade after some variant of the TPP become a reality.
Keywords: Trans-Pacific Partnership (TPP), Gravity Model, New Zealand